LANDASAN QUR'ANI DALAM HUBUNGAN ANTAR AGAMA: TITIK TEMU HERMENEUTIKA GERAK GANDA DAN TAFSIR FILOSOFIS THABATHABAI - Amrizal Amrizal (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2020)
This article discusses the Fazlur Rahman and Thabathabai thought on Qur'anic verses that can be used as a basis for interfaith relations. The discussion focused on their methodology of interpretations and responses to conventional Qur'anic interpretations. Fazlur Rahman with his double movement hermeneutics and Thabathabai with his philosophical interpretation. Although hermeneutics and interpretation are often disputed, the interpretation of these two figures has a common point that can be synthesized through logical dialectics. Both of their attention to philosophy and critical responsestowards conventional methods of interpretation became a thesis for the synthesis process carried out. Hereby, it can be found a synthesis about the Qur'anic basis which can be used as a guide for Muslims in fostering relationships with other religions followers. In addition, they also provide guidelines related to the way for a Muslim to behave towards the adherents of other religions, without having to believe in the inevitability of practicing religious pluralism in terms of interfaith relation. This synthesis, if it is drawn into the interpretation methodology, it is seen that there is a correlation between the results of the double movement hermeneutics interpretation and philosophical interpretation, at least in the term of ethics.